2019
DOI: 10.1111/jocn.14866
|View full text |Cite
|
Sign up to set email alerts
|

Critical care nurses’ clinical reasoning about physiologic monitor alarm customisation: An interpretive descriptive study

Abstract: , H. (2019). Critical care nurses' clinical reasoning about physiologic monitor alarm customisation: An interpretive descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
(2 reference statements)
1
27
0
Order By: Relevance
“…Alarm management aims to prevent alarm fatigue by reducing the number of alarms, and the key to eliminating alarm fatigue is to increase the positive predictive rates of alarms or decrease the number of nonactionable alarms (Winters et al., 2018). Nurses are the primary users and maintainers of monitors (Ruppel et al., 2019); thus, their alarm management behaviour is key in determining the occurrence of nonactionable alarms and alarm fatigue. According to a previous study, 3%–40% of healthcare workers indicated they had never used many of the monitoring functions of a monitor (Sowan et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Alarm management aims to prevent alarm fatigue by reducing the number of alarms, and the key to eliminating alarm fatigue is to increase the positive predictive rates of alarms or decrease the number of nonactionable alarms (Winters et al., 2018). Nurses are the primary users and maintainers of monitors (Ruppel et al., 2019); thus, their alarm management behaviour is key in determining the occurrence of nonactionable alarms and alarm fatigue. According to a previous study, 3%–40% of healthcare workers indicated they had never used many of the monitoring functions of a monitor (Sowan et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some works discussed reducing alarm fatigue in NICUs by implementing delays between exceeding a threshold and the start of the alarm, or by using longer average periods for vital signs, to account for patient self-stabilization [16,21]. Other heuristic approaches aimed towards wider limits for alarm thresholds [25] or customizing them to patient characteristics [18,24]. However, these approaches do not use interaction of the caregiver with the system to investigate clinical relevance of an alarm.…”
Section: Related Workmentioning
confidence: 99%
“…Alarm fatigue can become so problematic that it has been named a medical device technology hazard [14]. On the one hand clinically relevant alarms should be handled while, to reduce alarm fatigue, alarms not clinically relevant and requiring no action should be reduced [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Even if alarms are actionable, we know that nurses may not always respond quickly for a variety of reasons 7 15–17. Factors like insufficient staffing, high severity of illness on the unit and unbalanced nursing skill mix all likely contribute to inadequate alarm response.…”
mentioning
confidence: 99%
“…Factors like insufficient staffing, high severity of illness on the unit and unbalanced nursing skill mix all likely contribute to inadequate alarm response. In critical care, nurses have reported that the nature of their work requires that they function as a team to respond to one another’s alarms 15. Although not ideal, nurses have developed heuristics based on factors like family presence at the bedside to help them prioritise alarm response in hectic work environments 7 16.…”
mentioning
confidence: 99%